Psychosocial Adjustment of First Year Gymnasium Students Depending on Gender - Šarūnas Klizas; Irina Klizienė; Vitas Linonis; Daina Miliauskienė (Lithuanian Sports University, 2018)
Research background and hypothesis. The data of students' national academic achievements confirmed that high achievements were related to good well-being at school. Most attention should be paid to first year gymnasium students because especially great differences were established in the academic achievements of those who evaluated school microclimate favorably and unfavorably. We hypothesized that the level of psychosocial adjustment of female first year gymnasium students would be higher than that of male students. Research aim. The aim of the present study was to establish psychosocial adjustment of first year gymnasium students depending on their gender. Research methods. The sample included 362 first year gymnasium students, girls (n  = 198) and boys (n = 164). They were 14-16 years of age. The Rogers and Dymond's questionnaire was chosen for the evaluation of psychosocial adjustment (Rogers, Dymond, 1954). It was translated into the Lithuanian language and adapted for the Lithuanian population (Klizas, 2009). Besides the psychosocial adjustment subscale, we analyzed other subscales (self-esteem, evaluation of others, emotional comfort, integrity, domination, avoidance of problem) as well which helped reveal the person's psychosocial adjustment. Research results. Analyzing the level of gymnasium students psychosocial adjustment in the aspect of gender, we established statistically significant difference in the avoidance of problems (t = -3.19; p < 0.05). We established that the level of negative evaluation of others for boys and girls was statistically significant (χ 2  = 10.71; df = 2; p < 0.05). The evaluation of the level of emotional discomfort for boys and girls revealed a statistically significant difference in the aspect of gender (χ 2 =  12.49; df = 2; p < 0.05). Discussion and conclusions. We established that psychosocial adjustment of first year gymnasium students was of low level. Such components of psychosocial adjustment as adjustment, evaluation of others, emotional comfort, integrity, domination and avoidance of problems were of low level, and only self-esteem was moderate. In the aspect of gender, we revealed a statistically significant difference in the avoidance of problems (p  < 0.05). The avoidance level of girls in the first year of the gymnasium was higher than that of boys. But for boys, the levels of adjustment, evaluation of others, emotional comfort, integrity, domination were higher than those of girls. Self-esteem for girls was higher than that of boys; however, no statistically significant difference was found. Keywords: school (adjustment) microclimate, emotional comfort, avoidance of problems.